Clinical and sonohysterography evaluation of infertile women - Pandit, Upendra; Baral, Lekhnath (Journal of Chitwan Medical College, 2020)
Background: Hysterosalpingography (HSG) is an integral part of the Conventional clinical evaluation of infertile women. Now a day, Sonohysterography is a modern technique widely used in the clinical evaluation. The objective of this study was to identify pelvic pathology; compare the effect and findings of tubal patency test between Sonohysterosalpingography and single film HSG radiograph. Methods: This is a prospective evaluation of infertile women who attended the infertility unit of the gynecology department from 2017 March to 2018 October. Women 220 clients were subjected to clinical including SHSG evaluation followed by a single film HSG radiograph on the single sitting. The Chi-square test, multinomial logistic regression analysis was done using IBM SPSS statistics version 20. Results: Women had bilateral tubal patency 181(82.2%) in SHSG and conformed the same number later by HSG. SHSG showed bilateral tubal occlusion in 33 (15%) whereas HSG conformed only in 22(10%) and block was seen in 18(8.18%) only by HSG. The pathological findings were polycystic ovaries in 33 (15%), Fibroid uterus 11 (5%), ovarian cysts 5(2%), endometrial polyps in 2 cases, endometriotic cyst with hydrosalpinx 8(4%). Procedural side effects were no pain in 69(31.1%), mild pain 125(56.3%), Moderate pain 21(9.5%), vasovagal symptoms 7(3.1%). Conclusions: The outcome of the Sonohysterosalpingraphy (SHSG) test for tubal patency is significantly synergized by concurrent HSG in the same sitting. The combined test is best indicated if SHSG alone is not able to demonstrate the sign of tubal patency.